Efficient access of replicated data in distributed database systems - Mustafa Mat Deris (Universiti Putra Malaysia, 2011)
Replication is a useful technique for distributed database systems where a data object will be accessed (i.e., read and written) from multiple locations such as from a local area network environment or geographically distributed world wide. This technique is used to provide high availability, fault tolerance, and enhanced performance.